International Capital Markets and Open-Economy Macroeconomics. - FitzGerald, E (1996)
The standard open-economy model on which the Bretton Woods macroeconomics is based takes into account neither the systemically fragmented nature of international capital markets nor the institutional relationship between savings and investment in semi-industrial economies. This paper suggests that a more realistic approach to these structural features, possibly along the lines suggested by recent "new-Keynesian" theories of market failure, would yield a model of macroeconomic behaviour which emphasizes investor uncertainty and vulnerability to external shock. The policy implications have interesting parallels with Keynes's own views on stabilization.